Harmonizing French and German administrative DADS-EDP and SIAB data - A practical guide on how to create comparable data sets on maternal employment - Filser, Andreas; Achard, Pascal; Amend, Inga; Frodermann, Corinna; Gaede, Ida; Wagner, Sander (International Journal of Population Data Science, 2026)
Administrative data is increasingly used in social science research, including for studying the labour market consequences of motherhood. Yet despite the growing use of such data within countries, cross-national comparative research remains limited because administrative data require substantial harmonisation before meaningful comparisons are possible. In this paper, we harmonise two rich administrative data sets suitable for comparative research on maternal employment: the French DADS-EDP and the German SIAB. Both data sets are based on social security records, span several decades, include detailed employment histories linked to firm-level data, and are accessible to the scientific community. France and Germany present a compelling case for comparison on maternal employment, given that both countries have followed different policy paths regarding childcare and norms around maternal employment. We illustrate the potential of the harmonised data by showing how maternal employment trajectories evolve over time in France, West Germany, and East Germany. Our results reveal sharp employment declines after childbirth in all three regions, but with significant variation in magnitude and recovery. French mothers experience relatively modest declines, while German mothers, especially in West Germany, face steeper short-term drops and slower recoveries. Over successive cohorts, employment penalties shrink in all three regions, with particularly marked decreases in Germany following the 2007 parental leave reform – notwithstanding continued differences between East and West Germany. These findings highlight the value of harmonised administrative data for understanding maternal employment in a comparative perspective against the background of policy reforms and enduring regional differences.